Friday
March 24, 2017

Post a New Question

Posted by on Friday, July 22, 2011 at 8:04pm.

solve by elimination x+6y=12
-x+7y=1

  • Algebra - , Saturday, July 23, 2011 at 8:55am

    x + 6y = 12 --- Equation 1

    -x + 7y = 1 --- Equation 2

    13y = 13

    y = 13/13

    y = 1


    sub y = 1 in equation 1 we get:

    x + 6y = 12

    x + 6(1)= 12

    x + 6 = 12

    x = 12 - 6

    x = 6

    Hence, x = 6 when y = 1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question